Structure and dynamics of aqueous 2-propanol: a THz-TDS, NMR and neutron diffraction study. Issue 45 (29th October 2015) - McGregor, James; Li, Ruoyu; Zeitler, J. Axel; D'Agostino, Carmine; Collins, James H. P.; Mantle, Mick D.; Manyar, Haresh; Holbrey, John D.; Falkowska, Marta; Youngs, Tristan G. A.; Hardacre, Christopher; Stitt, E. Hugh; et al.
Abstract : 90 molH2 O % is identified as a critical composition at which alcohol–water interactions are maximised; with 4–5 H2 O molecules present in the hydration shell per 2-propanol. Abstract : Aqueous liquid mixtures, in particular, those involving amphiphilic species, play an important role in many physical, chemical and biological processes. Of particular interest are alcohol/water mixtures; however, the structural dynamics of such systems are still not fully understood. Herein, a combination of terahertz time-domain spectroscopy (THz-TDS) and NMR relaxation time analysis has been applied to investigate 2-propanol/water mixtures across the entire composition range; while neutron diffraction studies have been carried out at two specific concentrations. Excellent agreement is seen between the techniques with a maximum in both the relative absorption coefficient and the activation energy to molecular motion occurring at ∼90 mol% H2 O. Furthermore, this is the same value at which well-established excess thermodynamic functions exhibit a maximum/minimum. Additionally, both neutron diffraction and THz-TDS have been used to provide estimates of the size of the hydration shell around 2-propanol in solution. Both methods determine that between 4 and 5 H2 O molecules per 2-propanol are found in the 2-propanol/water clusters at 90 mol% H2 O. Based on the acquired data, a description of the structure of 2-propanol/water across the composition range is presented.